Peran Profitabilitas (ROA) dalam Memoderasi Hubungan Struktur Modal (DER) dan Ukuran Perusahaan (SIZE) terhadap Nilai Perusahaan (PBV)Sektor Properti & Real Estate di BEI 2020-2024 - Puteri Kusuma Dewi; Diana Puspitasari; Dwi Eko Waluyo; Vicky Oktavia (Pusat Riset dan Inovasi Nasional, 2026)
This study evaluates the impact of capital structure (DER), company size (SIZE), and profitability (ROA) on firm value (PBV), while also examining the moderating role of ROA in the relationship between capital structure, company size, and firm value within the Indonesian property and real estate sector for the 2020–2024 period. Using panel data regression, the results indicate that DER, SIZE, and ROA each have a significant positive effect on firm value. Furthermore, ROA is proven to strengthen the influence of both capital structure and company size in enhancing firm value. These findings support Signaling Theory and Trade-Off Theory, confirming that efficient capital management and large company scale serve as positive signals for investors in the post-pandemic era. Practically, the results suggest that investors prioritize profitability as a key determinant when assessing investment prospects in the property sector.